Governing by campaigning the politics of the Bush presidency. - Edwards, George C (New York Pearson Longman, 2007)
This brief text, by one of the foremost experts on the presidency, explores how the Bush administration has attempted sweeping changes in public policy - without broad support for doing so - by taking its case to the American public more than any other president in history.--BOOK JACKET.
Policy and polarization: the context of governing -- Going public : a strategy for governing -- Persuading the public -- Public opinion about the President -- Leading in Congress -- Reforming social security, part I : going public -- Reforming social security, part II : persuading the public and Congress -- Governing by campaigning.
Includes bibliographical references and index.
Donated by Logan Wangsgard (Hall's Book Drive) Dec. 2015.
Keywords: Bush, George W. (George Walker), 1946-.; United States -- Politics and government -- 2001-2009.